Geographic differences in outcomes in outpatients with established atherothrombotic disease: results from the REACH Registry. (29th August 2020) - Ducrocq, G; Bhatt, DL; Labreuche, J; Corbalan, R; Porath, A; Gao, R; Panchenko, E; Liau, CS; Ikeda, Y; Goto, S; Amarenco, P; Steg, PG
Abstract: Aims: There are major differences in the prevalence and management of patients with atherothrombotic disease including coronary artery disease (CAD), cerebrovascular disease (CVD) and peripheral artery disease (PAD) across different geographical regions. There is, however, little data allowing comparisons of management and outcomes across broad geographic regions. We aimed to describe geographical differences in baseline characteristics, management and outcomes in stable outpatients with established atherothrombotic disease. Methods and results: From the REACH Registry of atherothrombosis, patients with documented CAD, PAD or CVD and with 4-year follow-up were included. Baseline characteristics, treatments and 4-year outcomes were recorded. Event rates were compared between geographical regions and were adjusted for risk scores predicting ischemic and bleeding events. The analyses of baseline characteristics and medications according to geographical region showed marked differences. For the composite primary outcome (cardiovascular death, non-fatal myocardial infarction (MI) and non-fatal stroke), rates ranged from 12.1% in Japan to 18.2% in Eastern Europe. After adjustment, substantial variations remained: taking North America as a reference, patients from Western Europe and Japan had a lower risk of primary outcome event (hazard ratio (HR) 0.93; p  = 0.045, and HR = 0.67; p  < 0.001 respectively) whereas patients from Eastern Europe had a higher risk (HR = 1.24; p  < 0.001). There were no obvious differences between patients from North America and those from Latin America, the Middle East and Asia. Conclusion: There are important variations in the outcomes of patients with atherothrombotic across geographic regions. These observations have important implications for public health and clinical research.